2016
DOI: 10.14238/pi45.6.2005.270-4
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity: Prevalence and risk factors

Abstract: Background Retinopathy of prematurity (ROP) is one of the ma-jor causes of infant blindness. There are several factors known asrisk factors for ROP. Recent studies show ROP as a disease ofmultifactorial origin.Objective To report the prevalence of ROP in Cipto MangunkusumoHospital, Jakarta and its relation to several risk factors.Methods A cross-sectional descriptive study was conducted fromDecember 2003-May 2005. All infants with birth weight 2500 gramsor less, or gestational age 37 weeks or less, were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The incidence of ROP grade III or higher was 4.8%, 9.6% and 10% in the three studies that reported these data [6,8,9], and 3.6% in our own hospital. Risk factors for the development of ROP were asphyxia, blood transfusions, oxygen therapy for more than 7 days, sepsis, PDA, and a gestational age of <28 weeks [6][7][8][9]. In our search, we also identified one paper indicating that ROP contributed to 1.1% of all cases of blindness in children in Indonesia [13,14].…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…The incidence of ROP grade III or higher was 4.8%, 9.6% and 10% in the three studies that reported these data [6,8,9], and 3.6% in our own hospital. Risk factors for the development of ROP were asphyxia, blood transfusions, oxygen therapy for more than 7 days, sepsis, PDA, and a gestational age of <28 weeks [6][7][8][9]. In our search, we also identified one paper indicating that ROP contributed to 1.1% of all cases of blindness in children in Indonesia [13,14].…”
Section: Resultssupporting
confidence: 53%
“…The incidence of ROP in the other reports ranged from 12.5%-33.3% [10][11][12]. The incidence of ROP grade III or higher was 4.8%, 9.6% and 10% in the three studies that reported these data [6,8,9], and 3.6% in our own hospital. Risk factors for the development of ROP were asphyxia, blood transfusions, oxygen therapy for more than 7 days, sepsis, PDA, and a gestational age of <28 weeks [6][7][8][9].…”
Section: Resultsmentioning
confidence: 46%
See 2 more Smart Citations